Yellow fever: laboratorial diagnosis and clinical manifestations - Analúcia R. Xavier; Gabriela S. Freitas; Caroline F. Santos; Werlley A. Januzzi; Gilmar S. Lacerda; Edimilson R. M. Carvalho; Salim Kanaan (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Yellow fever is an infectious disease of acute evolution, initially non-contagious, transmitted by a ribonucleic acid (RNA) virus that belongs to the Flaviviridae family. In the period from December 2016 until March 17, 2017, 1, 561 suspected cases of wild yellow fever were reported to the Ministry of Health in Brazil. Among these cases, 850 (54.8%) remain under investigation, 448 (28.7%) were confirmed and 263 (16.9%) were discarded. Out of the total cases reported, 264 died, 144 (54.5%) were confirmed for the disease, 110 (41.7%) were investigated and 10 (3.8%) were discarded. The case fatality rate among confirmed cases was 32.2%. The specific diagnosis for determining the etiology of infection can be made by demonstrating the humoral response of the antibodies, virus isolation, or histopathological study of the liver. Only through early laboratory diagnosis and epidemiological data supply can government and cooperative organizations establish public policies to combat future disease epidemics, as well as social awareness campaigns.